2020
DOI: 10.1101/2020.06.18.159822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 Gag protein with or without p6 specifically dimerizes on the viral RNA packaging signal

Abstract: The HIV-1 Gag protein is responsible for genomic RNA (gRNA) packaging and immature viral particle assembly. While the presence of gRNA in virions is required for viral infectivity, in its absence, Gag can assemble around cellular RNAs and form particles resembling gRNA-containing particles. When gRNA is expressed, it is selectively packaged despite the presence of excess host RNA, but how it is selectively packaged is not understood. Specific recognition of a gRNA packaging signal (Psi) has been proposed to st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The VP40-nucleic acid complexes have well-defined stoichiometry In order to understand the biologically possible VP40-nucleic acid complexes, we set out to determine the VP40 oligomeric states corresponding to protein bands visible in our blue native protein gels, as well as the stoichiometry by which nucleic acid oligos can combine with VP40. This led us to examine our VP40 samples using native mass spectrometry (nMS) (Katta and Chait, 1991;Heck, 2008;Liko et al, 2016;Sarni et al, 2020).…”
Section: Accessmentioning
confidence: 99%
“…The VP40-nucleic acid complexes have well-defined stoichiometry In order to understand the biologically possible VP40-nucleic acid complexes, we set out to determine the VP40 oligomeric states corresponding to protein bands visible in our blue native protein gels, as well as the stoichiometry by which nucleic acid oligos can combine with VP40. This led us to examine our VP40 samples using native mass spectrometry (nMS) (Katta and Chait, 1991;Heck, 2008;Liko et al, 2016;Sarni et al, 2020).…”
Section: Accessmentioning
confidence: 99%
“…Our relatively simple assays of the base order-dependent component of the folding energy, which are devoid of redundant base compositional information (see Materials and Methods), have shown that a highly conserved region, in otherwise rapidly mutating HIV-1 genomes, associates with an RNA structure corresponding, not to a protein-encoding function, but to an RNA packaging signal. The latter is specifically recognized by the nucleocapsid domain of the Gag polyprotein (Sarni et al, 2020) and is now seen as a potential "Achilles heel" of HIV-1 that can be targeted by a recently described antiviral compound (Ingemarsdotter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%